A complicated case of amyand's hernia involving a perforated appendix and its management using minimally invasive laparoscopic surgery: A case report. (2016) - Al-Ramli, Wisam; Khodear, Yahya; Aremu, Muyiwa; El-Sayed, Abdel Basset
Highlights: Laparoscopic surgery is frequently diagnostic as well as therapeutic in equivocal cases of right iliac fossa pain. Further delay in the decision of laparoscopic exploration in case of perforated Amyand's hernia would mandate an open exploration due to generalised peritonitis. Successful management of complicated case of Amyand's hernia involving a perforated appendix is feasible using a laparoscopic appendectomy approach. Abstract: Introduction: Amyand's hernia is a rare condition of inguinal hernia in which the appendix is incarcerated within the hernia sac through the internal ring. Complications include acute appendicitis and perforated appendicitis, which are rare in incidence, accounting for about 0.1% of cases. 1 These complications prove a diagnostic challenge due to their vague clinical presentation and atypical laboratory and radiological findings. Until recently, open appendectomy was the mainstay of treatment. Laparoscopic surgery offers a less invasive approach to confirming a diagnosis and serving as a therapeutic tool in equivocal cases. Case presentation: We report a case of a previously healthy 20-year-old male presenting with atypical signs and symptoms, as well as blood investigation results, and radiological findings of a perforated appendix within an Amyand's hernia. The patient was successfully managed using a minimally invasive laparoscopic appendectomy approach. Discussion: Until recently, open appendectomy was considered the mainstay in the management of complicated Amyand's hernia. Laparoscopic surgery provides a new avenue for dealing with diagnostic uncertainty with advantages including faster recovery time, reduced hospital stay, and better quality of life. Conclusion: This case report highlights the concealing effects of an Amyand's hernia on a perforated appendix, the considerations required when an equivocal diagnosis present and the safe use of the minimally invasive laparoscopic surgery in the treatment of this rare condition.